The management of upper gastrointestinal bleeding in hemophilia patients by sclerotherapy - Nadir YÖNETÇİ and Mustafa YILMAZ and Ömer ÖZÜTEMİZ and Fulya GÜNŞAR and Ayhan DÖNMEZ and Oktay TEKEŞİN and Yücel BATUR and Hanefi ÇAVUŞOĞLU (Turkish Journal of Gastroenterology, 2019)
-